2013
DOI: 10.3382/ps.2012-02308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clinoptilolite and modified clinoptilolite on the growth performance, intestinal microflora, and gut parameters of broilers

Abstract: The purpose of this study was to evaluate the effect of natural clinoptilolite (NCLI) and modified clinoptilolite (MCLI) on broiler performance, gut morphology, and its relation to gut circumstances. A total of two hundred forty 1-d-old male chicks were randomly assigned to 3 treatments, each of which comprised 8 pens of 10 chicks per pen. Birds in the control group were fed the basal diet, whereas those in the experimental groups were fed diets supplemented with NCLI at 2% (NCLI group) or MCLI at 2% (MCLI gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 35 publications
6
64
0
Order By: Relevance
“…1, where differences among treatments are slight and hence are not observable. These results are similar to those reported by Wu et al (2013) who evaluated the effect of dietary supplementation with 2% natural and modified clinoptilolite on broiler performance, as well as the results reported by Öztürk et al (1998) who found something similar in an experiment where they fed a diet supplemented with a natural zeolite to laying hens.…”
Section: Feed and Water Consumption And Feed Conversion Ratiosupporting
confidence: 81%
“…1, where differences among treatments are slight and hence are not observable. These results are similar to those reported by Wu et al (2013) who evaluated the effect of dietary supplementation with 2% natural and modified clinoptilolite on broiler performance, as well as the results reported by Öztürk et al (1998) who found something similar in an experiment where they fed a diet supplemented with a natural zeolite to laying hens.…”
Section: Feed and Water Consumption And Feed Conversion Ratiosupporting
confidence: 81%
“…Zeolite has a beneficial effect on feed components owing to the fact that they improve energy and protein retention. Zeolite influences nutrient absorption in the digestive tract allowing for better results than other supplements (Wu et al, 2013a). Zeolite as a dietary supplement in poultry showed that animals mostly grow faster, and the number and severity of intestinal diseases are reduced (Pavelic et al, 2001).…”
Section: Effect Of Feeding Transcarpathian Zeolite On Gastrointestinamentioning
confidence: 99%
“…Natural zeolites are crystalline aluminosilicates with unique adsorption, cationexchange (Wu et al, 2013a). Zeolite has a unique structure, which is similar to that of a honeycomb, and each tiny cavity within every piece of zeolite is negatively charged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard of the pH of the content from each compartment of the gastrointestinal tract, one bird at time per plot in fasting, was weighted and slaughtered by cervical dislocation, in a total of 10 individuals for pH analysis. All the procedures to obtain the pH of the content of every compartment of the gastrointestinal tract was conferring as suggested by Wu et al (2013). Immediately after the slaughter of the birds, the viscera was exposed, so the organs necessary to the analysis could be identified: goiter, proventriculus, gizzard, duodenum, jejunum, ileum, cecum and colon.…”
mentioning
confidence: 99%